Design and analysis of metamaterial-inspired annular ring patch antenna for 5G applications - Vishu Vidyadharan; Sivagnanam Sivaramalingam; Lekshmi Kanthan Padma Suresh (Bulletin of Electrical Engineering and Informatics, 2026)
This work presents an annular ring patch antenna (ARPA) on the basis of metamaterial (MTM) for 5G applications. ARPA has become a popular choice for a range of wireless applications owing to its low profile, miniature size, simplicity in integrating with printed circuit boards (PCBs), and compatibility with contemporary fabrication techniques. Nevertheless, the bandwidth, gain, and efficiency restrictions that the ARPA frequently experiences are crucial for fulfilling the stringent needs of 5G communication systems. To overcome these obstacles, researchers have tuned to materials known as MTMs, which are synthetic materials having special electromagnetic (EM) characteristics absent from natural materials. By including complementary split ring resonators (CSRR) structures into microstrip patch antenna (MPA) the important characteristics like bandwidth, gain, and efficiency are enhanced. An EM simulation software named computer simulation technology (CST) Microwave Studio is employed for the evaluation of the antenna prototype. Rogers RT5880, a commercially accessible substrate material is used to develop the prototype. Comparative analysis is conducted between conventional antennas and ARPA, in which the proposed antenna attains low electrical loss, uniform electrical properties, thermal stability, and dimensional stability with gain of 5.65 dB. The developed work proves that the addition of CSRR structure is the solution to the development of antennas with superior performance characteristics.